Responsibilities of Notaries in the Deed of Sale and Purchase Agreement for Land and Buildings Made in Front of a Notary - Rima Dian Permata; Hasim Purba; Agustining; Mahmud Mulyadi (Jurnal Ragam Pengabdian, 2026)
Notaries as public officials are authorized to make authentic deeds and are obliged to carry out their duties according to the principle of prudence as stipulated in Article 16 paragraph (1) letter a jo. Article 39 paragraph (2) of the Law on the Notary Position (UUJN). In this study, it was found that Notaries do not fully apply this principle, so that the deed made has the potential to cause losses for the parties. The formulation of the problem includes: the legal responsibility of the Notary in the agreement of sale and purchase of land and buildings; legal protection for good-faith buyers; as well as the analysis of the legal considerations of the panel of judges in Decision Number 179/PDT/2018/PT BTN. This study uses a normative juridical method with an analytical descriptive nature, aiming to describe and analyze the relationship between legal norms through literature studies. The results of the study show that Notaries can be held to be held civil liable if they are proven to be not thorough and not careful in making deeds, thus causing losses, in the form of the obligation to reimburse costs and losses. Legal protection for buyers in good faith is highly dependent on the substance of the Binding Sale and Purchase Agreement (PPJB). The judge's consideration in the decision assessed that the Notary had checked and the parties did not raise objections until the process of signing and minutation of the deed was completed